1983
DOI: 10.1677/joe.0.0970327
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of the selective suppression of plasma levels of follicle-stimulating hormone in the female rat after administration of steroid-free bovine follicular fluid

Abstract: Steroid-free bovine follicular fluid (bFF) selectively suppresses the plasma levels of FSH in the female rat, demonstrating that bFF contains inhibin-like material. The present study was concerned with the effects of bFF on the hypothalamic release of LH releasing hormone (LH-RH) into hypophysial stalk blood and on the metabolic clearance rates of gonadotrophins. The metabolic clearance rates of FSH, LH and prolactin were determined after a single injection of and during a constant infusion with adenohypophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
3
21
1
Order By: Relevance
“…A larger difference was found in the circulatory T Y of rat FSH between the earlier findings on pituitary (40路5 min; de Greef et al 1983) and recFSH (88路4 min). The reason for the difference is not apparent, since pituitary FSH and recFSH should be structurally closer, due to the fact that the carbohydrates of FSH are not sulfated in the same way as those of LH.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A larger difference was found in the circulatory T Y of rat FSH between the earlier findings on pituitary (40路5 min; de Greef et al 1983) and recFSH (88路4 min). The reason for the difference is not apparent, since pituitary FSH and recFSH should be structurally closer, due to the fact that the carbohydrates of FSH are not sulfated in the same way as those of LH.…”
Section: Discussioncontrasting
confidence: 72%
“…De Greef et al (1983) have reported previously a half-time of 18路6 min for rat LH after injection of adenohypophysial extracts in female rats. These data on LH are surprisingly similar to the T Y values measured for rat recLH in our study (18路2 min).…”
Section: Discussionmentioning
confidence: 95%
“…This has been proven true for the pituitary gland, since intact hemi-pituitaries exhibit a greater hormonal responsiveness than dispersed pituitary cells (Milenkovic et al 1989). Despite early studies suggesting a hypothalamic site of inhibin action (Lumpkin et al 1981, Condon et al 1983, Greef et al 1983, we and others (Gonzalez-Manchion et al 1991, Knight 1996 have been unable to find any effect of inhibin on basal GnRH release. This finding may support the hypothesis that the main site of inhibin action is the pituitary (Tilbrook et al 1993).…”
Section: Discussionmentioning
confidence: 78%
“…In addition to a pituitary site of action, effects of activins and inhibins on the release and/or biosynthesis of hypothalamic GnRH release have been suggested (Lumpkin et al 1981, Condon et al 1983, Greef et al 1983. The recent demonstration that -subunits and the activin receptor ActRII mRNA are present in hypothalamic regions involved in the release of GnRH provided the neuroanatomical basis for a possible effect of activins on GnRH release and/or biosynthesis , Cameron et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, thirty-two rats per group as a minimum for measuring serum T is a much larger number than is commonly appreciated as necessary. For LH, Nett's approximation of a twenty-four-minute half-life is the higher end of the range of reported values, from thirteen to nineteen to twenty-three minutes (de Greef et al 1983;Weick 1977); in the following example, twenty minutes will be used as a representative number. Ellis and Desjardins (1982) give the range of interpulse intervals for LH as being from thirty-five to 360 minutes, with a mean of ninety-eight minutes.…”
Section: Measuring T and Lhmentioning
confidence: 99%